2004
DOI: 10.1088/0953-8984/16/9/003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the ramping rate on oxygen precipitation and the denuded zone in heavily doped Czochralski silicon

Abstract: The effect of the ramping rate on oxygen precipitation and the denuded zone in heavily doped Czochralski (CZ) silicon has been investigated. Wafers with different dopants (boron, arsenic and antimony) were subjected to a preannealing at 1150 • C and then ramping processes with different rates. It was found that along with the decrease of the ramping rates, the density of oxygen precipitates increased in all the heavily doped silicon wafers; however, the width of the denuded zone decreased in heavily boron dope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…[4][5][6][7][8] VO 2 complexes can act hereby as precursors for oxide precipitate nucleation at temperatures up to 1020 C. 2,9,10 It has been reported that OP in heavily As or Sb doped n-type Cz silicon is suppressed during conventional thermal annealing. [10][11][12][13][14][15] Whether the OP enhancement strategy based on RTP can be applied on heavily doped n-type Cz silicon needs to be clarified from a technological point of view. Moreover, it remains an open question whether the aforementioned VO 2 -complex-assisted oxide precipitate nucleation mechanism operates also in heavily doped n-type Cz silicon.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] VO 2 complexes can act hereby as precursors for oxide precipitate nucleation at temperatures up to 1020 C. 2,9,10 It has been reported that OP in heavily As or Sb doped n-type Cz silicon is suppressed during conventional thermal annealing. [10][11][12][13][14][15] Whether the OP enhancement strategy based on RTP can be applied on heavily doped n-type Cz silicon needs to be clarified from a technological point of view. Moreover, it remains an open question whether the aforementioned VO 2 -complex-assisted oxide precipitate nucleation mechanism operates also in heavily doped n-type Cz silicon.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, in heavily doped CZ-Si, the free carriers give rise to significant absorption, thus making Si opaque to infrared light in the wavelength region which is used to characterize oxygen in Si. As a result, the knowledge about OP in heavily doped silicon is still limited (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…1 Large diameter ͑e.g., 200 and 300 mm͒ Cz silicon wafers used in the advanced device processes are, however, moving toward lower initial interstitial oxygen concentration ͓͑O i ͔͒, which makes it harder to obtain sufficient oxygen precipitation during normal thermal cycles. [5][6][7] The RA treatment was developed as an efficient technique to generate high-density oxygen precipitates not only in conventional Cz silicon but also in heavily As or Sb doped Cz silicon. [5][6][7] The RA treatment was developed as an efficient technique to generate high-density oxygen precipitates not only in conventional Cz silicon but also in heavily As or Sb doped Cz silicon.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, several dedicated methods have been developed to enhance oxygen precipitation in order to increase the internal gettering ͑IG͒ capability of large diameter Cz silicon wafer, such as the use of intentionally introduced impurities, 2,3 rapid thermal anneal at elevated temperatures, 4 as well as the use of ramped anneal ͑RA͒ techniques. [5][6][7] It was proposed to replace the conventional high-low-high IG process because the thermal budget at device processes is decreased and only a little annealing time is needed for oxygen precipitation. [5][6][7] It was proposed to replace the conventional high-low-high IG process because the thermal budget at device processes is decreased and only a little annealing time is needed for oxygen precipitation.…”
Section: Introductionmentioning
confidence: 99%